Inflow and outflow from the accretion disc of the microquasar SS433 - Sebastian Perez, M; Blundell, K (2008)
A succession of near-IR spectroscopic observations, taken nightly throughout an entire cycle of SS 433's orbit with UKIRT, reveal (i) the persistent signature of SS 433's accretion disc, having a rotation speed of ∼ 500 kms-1and (ii) confirms the presence of the circumbinary disc recently discovered at optical wavelengths by Blundell, Bowler and Schmidtobreick (2008) and (iii) detects a much faster outflow than has previously been measured from the disc wind. Our relatively high spectral resolution at these near-IR wavelengths has enabled us to deconstruct the different components, and their physical origins, that comprise the Brackett-γ line in this binary system. © Copyright owned by the author(s) under the terms of the Creative Commons Attribution-NonCommercial- ShareAlike Licence.